Were Online Media Biased? An Assessment of Statement and Actor Bias During the 2015 Referendum in Greece - Milioni, Dimitra L.; Spyridou, Lia Paschalia; Triga, Vasiliki (My University, 2024)
Referendum campaigns are highly mediated events likely to influence voters’ propensity to opt for “yes” or “no.” Media bias commonly refers to coverage that deviates from the norms of balance, fairness, and impartiality. Despite its widespread use, the notion of bias is quite complex, carrying multiple meanings and measurements. We define overall bias as the advocacy of “yes” and “no” vote choices expressed through statement and actor bias. Drawing on a quantitative analysis of the 2015 bailout referendum in Greece, we show that although overall online coverage was not biased, media type had a significant effect on the presence of bias. Legacy media favored the “yes” vote choice, alternative media skewed toward the “no” vote choice, and web natives and the public broadcaster maintained a balanced approach. Probing further, we found that alternative media produced biased content mainly through statement bias, while legacy media’s pro-yes tilt was predominantly performed through actor bias.
Keywords: Media bias; Referendum campaign; Statement bias; Actor bias; Objectivity; Sources; Greek bailout referendum